ALQURAN DAN RAHASIA ANGKA: Kajian Kitab Tafsir Karya Abu Zahra al-Najdi - Muhammad Akrom Adabi (UIN Siber Syekh Nurjati Cirebon, 2019)
The studies of miracles of the Qurâ€™an have long been dominated by the composition of the versatility, the selection of discussions and the placement of balanced vocabulary, all of which extinguish the miracles of the Qurâ€™an language. The studies continue to develop and emerge the studies of miracles of the Qurâ€™an by looking at the mathematical miracles in the Qurâ€™an. The miracles in the Qurâ€™an were first introduced by Rashad Khalif by discovering the miracles of numbers in Qurâ€™an verses. Some other studies tried to reveal the miracles of the Qur'an through matching and shifting certain aspects in Qur'an. Unlike in the previous studies, Abu Zahra An-Najd tried to relate words with the phenomenon of mathematical miracles that had been studied previously. This study tries to amend Iâ€˜jÄz â€˜adadÄ« in the Qur'an and the Secret Book of Abu Zahra an-Najdi.